The Effect of Project Based Learning Model Integrated with Padlet on Students’ Writing Skill - Nasution, Feny Meyla; Zulkarnain , Iskandar; Lubis , Sofia Idawati (English Education Study Program FKIP Universitas Alwashliyah Medan, 2024)
The objective of this study is to find out whether there is a significant effect of using Project Based Learning integrated with Padlet on students’ writing skill. This study because students' writing skill are still low due to lack of interest in learning English. They also find it difficult to organize ideas logically and convey them in a way that appeals to the reader. Then, in teaching learning process teacher still applied conventional learning method. This research uses quantitative method. The research design conducted in this study is to use an experimental design consisting of two classes, namely the experimental class and the control class. The experimental class was treated with Project Based Learning integrated with Padlet, the control class was not, but instead used the conventional method. The researcher conducted a pre-test and post-test on both classes. The results of the Independent Samples t-test showed significance value (2-tailed) of 0.000, which is less than 0.05, indicating a significant difference between the two classes. Thus, the alternative hypothesis (Ha) is accepted, and the null hypothesis (Ho) is rejected. It means the Project Based Learning Model Integrated with Padlet has a significant effect on improving students' writing skills.